2023
DOI: 10.3390/ijerph20054476
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Fatigue and Its Sociodemographic, Mental Health Status, and Perceived Causes: A Cross-Sectional Study Nearing the Transition to an Endemic Phase in Malaysia

Abstract: This study aimed to explore the socio-demographic characteristics, mental health status, and perceived causes of pandemic fatigue with COVID-19 pandemic fatigue among the general population of Malaysia. The data was collected online during the transition from the COVID-19 pandemic phase to the endemic phase in Malaysia from 1 to 30 April 2022. Sociodemographic data, Depression Anxiety Stress Scale-21 (DASS-21), perceived causes of pandemic fatigue, and the Fatigue Assessment Scale (FAS) were included in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…The pandemic introduced a range of stressors that affected people of all age groups, socio-economic backgrounds, and walks of life. The fear of infection, loss of loved ones, economic instability, pandemic fatigue, and disruption of daily routines contributed to heightened psychological distress (1)(2)(3)(4). Lockdowns and social distancing measures enforced isolation, depriving individuals of their usual social interactions and support systems.…”
Section: Impact Of Pandemicsmentioning
confidence: 99%
“…The pandemic introduced a range of stressors that affected people of all age groups, socio-economic backgrounds, and walks of life. The fear of infection, loss of loved ones, economic instability, pandemic fatigue, and disruption of daily routines contributed to heightened psychological distress (1)(2)(3)(4). Lockdowns and social distancing measures enforced isolation, depriving individuals of their usual social interactions and support systems.…”
Section: Impact Of Pandemicsmentioning
confidence: 99%
“…This phase was where nearly all social activities, education and business sectors were reopened at a condition where the occupancy rate could be achieved within 60% to 100% based on the vaccination status of employees [Ministry of Communication and Multimedia Malaysia (MCMC), 2022]. On 8 March 2022, the Prime Minister of Malaysia announced that the nation shifted to the endemic phase, where borders reopened on 1 April 2022 (Abdul Rashid et al, 2023). Timbuong et al (2021) reported that crowds in shopping malls were growing bigger due to the reopening of the economic sector and borders.…”
Section: Introductionmentioning
confidence: 99%
“…After a few months of lockdown periods, the numbers of COVID-19 cases continue to rise, with new COVID-19 variants causing the pandemic period to continue unexpectedly longer. Therefore, humans became demotivated and disobeyed the rules, which is evident in some countries (14,15,16). According to the WHO, this condition is known as pandemic fatigue (PF).…”
Section: Introductionmentioning
confidence: 99%